The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acs.analchem.6b00255
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of (Mixed) Halogenated Dibenzo-p-Dioxins by Negative Ion Atmospheric Pressure Chemical Ionization

Abstract: Brominated and mixed halogenated dibenzo-p-dioxins (PBDDs and PXDDs) may well be as toxic as 2,3,7,8-tetrachloro-dibenzo-p-dioxin (2378-TCDD), a compound reputed as one of the most toxic chemicals known to exist. However, studies on the occurrence of PXDDs have been hampered by a lack of authentic standards as well as separation techniques capable of resolving the enormous number of potential isomers. Electron ionization (EI) mass spectrometry based methods are of limited value due to the lack of isomer specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Unfortunately, this is often difficult information to get, especially with electron ionization mass spectrometry. Alternative ionization approaches can be helpful; for example, isomeric dioxin congeners can be differentiated by reactions with dioxygen anions …”
mentioning
confidence: 99%
“…Unfortunately, this is often difficult information to get, especially with electron ionization mass spectrometry. Alternative ionization approaches can be helpful; for example, isomeric dioxin congeners can be differentiated by reactions with dioxygen anions …”
mentioning
confidence: 99%
“…Therefore, separating toxic from non-toxic isomers is a major challenge that cannot be solved using GC alone, as witnessed by the coeluting isomers 2,3,7,8-TBDD (toxic) and 1,2,3,4-TBDD (less toxic) in Figure 5d. Fernando et al [103] showed that ion-molecule reactions with oxygen could be exploited to separate the coeluting isomers because 2,3,7,8-TBDD reacts with oxygen to produce the ether cleavage product C6H2BrO2 •− (m/z 265.840), whereas 1,2,3,4-TBDD cannot. When Structure-diagnostic reactions have also been observed in the positive ion mode 68 .…”
Section: Ion-molecule Reactions For Separation and Structural Elucidationmentioning
confidence: 99%
“…The current instrument configuration generates soft ionization fragments that differ from traditional electron impact (EI) ionization. Fernando et al 10 showed that polyhalogenated dibenzo-p-dioxins and furans (PXDDs and PXDFs) undergo an oxygen displacement reaction and produce pseudomolecular ions [M − X + O] − (where X = Cl, Br) using an APGC source in negative mode. A similar reaction product ion [M − Br + O] − was observed in PBDEs, although it was not always the most abundant fragment (Table S were not detected or had very low intensities in negative mode.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Softer ionization such as atmospheric pressure chemical ionization (APCI) methods generate fewer fragments and potentially produce a more intense molecular ion that may aid in the identification of an unknown through reconstruction of the molecular formula from the measured mass-to-charge (m/z) and observed isotopic distribution profile. 9,10 However, data processing for soft ionization high-resolution mass spectrometry (HRMS) data could be a challenge when confirmatory fragments are not available to support nontargeted analyses. The natural abundance of the two prominent isotopes of Br ( 79 Br, 81 Br) and Cl ( 35 Cl, 37 Cl) provide distinct M, M + 2, M + 4... isotopic signatures for compounds that contain these atoms.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation